Medicolegal issues of Mermaid syndrome (Sirenomelia) - M Vidanapathirana; KMTB Gjunathilaka (Anuradhapura Clinical Society, 2014)
Sirenomelia is a rare congenital deformity in which the legs are fused together giving them the appearance of a mermaid's tail. It is usually fatal within a day or two of birth. We describe a mermaid syndrome in a baby born to a 38 year old mother by lower segment cesarean section. This is her second pregnancy and first child died with meconium aspiration. Antenatal diagnosis of this condition has failed in this case in spite of routine Ultra Sound scan. However, because of her advance age anomaly scan could have done. There is an obvious chance of missing the diagnosis of mermaid syndrome during the routine examinations. Even it was diagnosed early; there are no legal provisions for a legal abortion unless the mother's life is in danger. Amendments to the existing laws of legal abortion by including at least fatal congenital anomalies as an indication and making the anomaly scan more regular are suggested to uphold the rights of mothers.